(untitled) (CIPEEX, 2025)
The observational study, conducted in April 2024 on the Marimba Coast, Amazonas, was part of a university extension project of the UniEVANGELICA, University of Anápolis-GO, in partnership with the Asas de Socorro Organization. The team, composed of volunteers from the fields of medicine, dentistry, nursing, and physical therapy, used a hospital boat to serve the riverside community, offering medical and dental care. Poor oral health conditions were identified, such as high rates of tooth decay and advanced periodontal disease, and challenges such as a lack of radiographic examinations and adequate clinical facilities were faced. Interventions in schools included guidance for teachers and students on oral health, with a view to longitudinal care. The project highlighted the isolation of riverside communities and the need for innovative solutions to improve access to health services.